COMPARING HYPNOBREASTFEEDING AND OXYTOCIN MASSAGE EFFECTIVENESS ON BREAST MILK PRODUCTION - Sari, Putri Permata; Aninora, Novia Rita; Wikarya, Rionitara (JURNAL KESEHATAN REPRODUKSI, 2025)
Background: Low exclusive breastfeeding rates are driven by maternal stress, fatigue, and low confidence, which hinder milk production. Non-pharmacological interventions are essential to enhance production. Objective: This study aims to determine the effectiveness of hypnobreastfeeding and oxytocin massage on breast milk production in nursing mothers. Method: The study design used a quasi-experimental two-group pretest–posttest design. The sample consisted of 32 breastfeeding mothers with infants aged 0–6 months, selected using consecutive sampling, with 16 respondents in each intervention group. The hypnobreastfeeding and oxytocin massage interventions were given for 15–20 minutes per day for 10 days. Breast milk production was measured through the frequency of urination and the increase in infant weight. Data were analyzed using an independent t-test. Results: The results showed the average weight of infants in the hypnobreastfeeding group was 5826.255 grams, while that in the oxytocin massage group was 6080.00 grams (p=0.001). The frequency of urination in the hypnobreastfeeding group was 8.71 times and in the oxytocin massage group was 8.81 times (p=0.000). Conclusion: Hypnobreastfeeding and oxytocin massage are effective in increasing breast milk production, but oxytocin massage results in a higher increase in infant weight gain, making it more recommended to support successful breastfeeding.